Properties of the QCD thermal transition with Nf=2+1 flavors of Wilson quark - Gert Aarts (Physical Review D, 2022)
We study properties of the thermal transition in QCD, using anisotropic, fixed-scale lattice simulations with Nf=2+1 flavors of Wilson fermion. Observables are compared for two values of the pion mass, focusing on chiral properties. Results are presented for the Polyakov loop, various susceptibilities, the chiral condensate and its susceptibility, and the onset of parity doubling in the light and strange baryonic sector.